Pasireotide Long‐Acting Release Treatment for Diabetic Cats with Underlying Hypersomatotropism. (1st February 2017) - Gostelow, R.; Scudder, C.; Keyte, S.; Forcada, Y.; Fowkes, R.C.; Schmid, H.A.; Church, D.B.; Niessen, S.J.M.
Abstract : Background: Long‐term medical management of hypersomatotropism (HS) in cats has proved unrewarding. Pasireotide, a novel somatostatin analogue, decreases serum insulin‐like growth factor 1 (IGF‐1) and improves insulin sensitivity in cats with HS when administered as a short‐acting preparation. Objectives: Assess once‐monthly administration of long‐acting pasireotide (pasireotide LAR) for treatment of cats with HS. Animals: Fourteen cats with HS, diagnosed based on diabetes mellitus, pituitary enlargement, and serum IGF‐1 > 1000 ng/mL. Methods: Uncontrolled, prospective cohort study. Cats received pasireotide LAR (6–8 mg/kg SC) once monthly for 6 months. Fructosamine and IGF‐1 concentrations, and 12‐hour blood glucose curves (BGCs) were assessed at baseline and then monthly. Product of fructosamine concentration and insulin dose was calculated as an indicator of insulin resistance (Insulin Resistance Index). Linear mixed‐effects modeling assessed for significant change in fructosamine, IGF‐1, mean blood glucose (MBG) of BGCs, insulin dose (U/kg) and Insulin Resistance Index. Results: Eight cats completed the trial. Three cats entered diabetic remission. Median IGF‐1 (baseline: 1962 ng/mL [range 1051–2000 ng/mL]; month 6: 1253 ng/mL [524–1987 ng/mL]; P < .001) and median Insulin Resistance Index (baseline: 812 μmolU/L kg [173–3565 μmolU/L kg]; month 6: 135 μmolU/L kg [0–443 μmolU/L kg]; P = .001) decreased significantly. No significant change was found in mean fructosamine (baseline: 494 ± 127 μmol/L; month 6: 319 ± 113.3 μmol/L; P = .07) or MBG (baseline: 347.7 ± 111.0 mg/dL; month 6: 319.5 ± 113.3 mg/dL; P = .11), despite a significant decrease in median insulin dose (baseline: 1.5 [0.4–5.2] U/kg; 6 months: 0.3 [0.0–1.4] U/kg; P < .001). Adverse events included diarrhea (n = 11), hypoglycemia (n = 5), and worsening polyphagia (n = 2). Conclusions and Clinical Importance: Pasireotide LAR is the first drug to show potential as a long‐term management option for cats with HS.